Cerebrospinal Fluid Presepsin As a Marker of Nosocomial Infections of the Central Nervous System: A Prospective Observational Study - Abudeev, Sergey A.; Kiselev, Kirill V.; Kruglyakov, Nikolay M.; Belousova, Ksenia A.; Lobanova, Inna N.; Parinov, Oleg V.; Udalov, Yuriy D.; Zabelin, Maxim A.; Samoilov, Alexandr S.; Cesnulis, Evaldas; Killeen, Tim; Popugaev, Konstantin A. (Frontiers in Neurology, 2018)
Background: Nosocomial CNS infection (NI-CNS) is a common and serious complication in neurocritical care patients. Timely, accurate diagnosis of NI-CNS is crucial, yet current infection markers lack specificity and/or sensitivity. Presepsin (PSP) is a novel biomarker of macrophage activation. Its utility in NI-CNS has not been explored. We first determined the normal range of cerebrospinal (CSF) PSP in a control group without brain injury before collecting data on CSF PSP levels in neurocritical care patients. Samples were analysed in four groups defined by systemic and neurological infection status. Results: CSF PSP levels in 15 control patients without neurological injury were 50–100 pg/ml. Ninety-seven CSF samples were collected from 21 neurocritical care patients. In patients without NI-CNS or systemic infection, CSF PSP was 340.4±201.1 pg/ml. Isolated NI-CNS was associated with CSF PSP levels of 640.8±235.5 pg/ml, while levels in systemic infection without NI-CNS were 580.1±329.7 pg/ml. Patients with both NI-CNS and systemic infection had CSF PSP levels of 1047.7±166.2 pg/ml. In neurocritical care patients without systemic infection, a cut-off value of 321 pg/ml gives sensitivity and specificity for NI-CNS of 100% and 58.3% respectively. Conclusions: CSF PSP may prove useful in diagnosing NI-CNS but its current utility is as an additional marker only.